INNOVATIVE VECTORS OF BANKING SYSTEM DEVELOPMENT (World of finance, 2019)
Introduction. In a context of increasing competition in the banking sector, the systematic introduction of advanced products and technologies is a key to successful implementation of business models and the effective conquest and maintenance of relevant segments of the financial market. Therefore, the necessary condition for the effective operation of banks is the development and implementation of an appropriate innovation strategy aimed primarily at optimizing management of resource potential, better meeting existing customer needs, as well as the development and technical improvement of services for an adequate response to all new market demands in accordance with economic changes in the globalized environment.Purpose. The purpose of this article is to substantiate and systematize theoretical views on understanding the essence and main directions of development of the banking system on an innovative basis. The formation of an effective management system for innovation activities should become the most important condition for ensuring the efficiency of the work of commercial banks and achieving their competitive advantage both in the domestic market and in the globalized financial space.Results. The basic theoretical approaches to the assessment of the essence of innovation activity of banks are analyzed and systematized, and the necessity of its consideration from institutional positions for assessing the effectiveness of innovations is determined. The main vectors of activation of the innovation process in commercial banks are substantiated: 1) introduction of innovative banking products and improvement of existing services capable of satisfying the broadest possible range of consumers’ needs in the financial market; 2) change of the concept of advancement of banking services to the users, introduction of innovative methods of their sales and the latest marketing strategies; 3) modernization of organizational structures of the bank and its structural subdivisions in order to increase the efficiency of the operation and speed of implementation of management decisions.Conclusions. Banking institutions, when formulating their own strategy, should consider the innovative vector of development as the most important means of ensuring the stability of its functioning, economic growth and competitiveness, since the efficiency of the bank depends on its ability to meet certain customer’ needs. The results of implementation of such innovations may be reflected in expansion of the client base of the bank, optimization of its branch network and organizational structure, increase of the share of the financial market, reduction of transaction costs of banking operations, and also in ensuring the stability of the bank’s functioning in the long run.